Pengaruh Model Discovery Learning Pada Materi Interaksi Makhluk Hidup Terhadap Kemampuan Literasi Sains Siswa - Tri Pujiasih; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2020)
Abstract: The Effect Of Discovery Learning Model On Interaction Living Things Material On The Learners Scientific Abilities. The aim to determine the effect of Discovery Learning on interaction living things material grade VII stundents scientific literation skills at SMP Negeri 1 Kotaagung. The samples were 64 stundents VII I and VII J in the school year 2018/2019 selected by cluster sampling technique.Quantitatif data increasing the literacy skill of stundents obtained from the stundent’s answer to the 2006 question of PISA analyzed by performing scores and interpreting into table and chart criteria. Qualilative data comes from learner’s responses to discovery leraning its number of stundents answered then anlyzed by counting persentages and interpreting into table and chart criteria. Analysis shows that the effects of discovery learning influence on the stundents scientific literation abilities is increasing verry well with an average score of N-gain content aspects of the experiment 0,38 control 0,21. On average process aspect obtained by experiment 0,40 control 024 Result have shown thatlearning with discovery learning model has influenced the growth in the learner’s science skills better than applying the discussion learning model.Keywords :discovery learning, discussion, scientific literacy